Organocatalytic cycloaddition of carbonyl sulfide with propargylic alcohols to 1, 3-oxathiolan-2-ones. Issue 6 (4th March 2019) - Zhou, Hui; Zhang, Rui; Zhang, Hui; Mu, Sen; Lu, Xiao-Bing
Abstract : Lewis base-COS adducts were firstly studied as organocatalysts for the cyclization of propargylic alcohols with carbonyl sulfide. Abstract : A series of carbonyl sulfide (COS) adducts of a Lewis base (LB) were synthesized and first used to catalyze the cycloaddition of COS with propargylic alcohols under mild reaction conditions, selectively providing the functionalized 1, 3-oxathiolane-2-ones with complete ( Z ) configuration selectivity. Among them, COS adducts of highly polarized olefins proved to be highly efficient organocatalysts for this transformation, with excellent yields and wide functional group compatibility. Mechanistic investigations by isotope labeling and stoichiometric experiments incontrovertibly demonstrate that the catalytic reaction proceeds via a LB-COS adduct mediated nucleophilic addition mechanism. By combining the functions of gas capture (activation) and catalysts, this strategy provides a direction for cost-effective COS reduction processes.